FALSE MEMORIES IN ONLINE MISINFORMATION EXPERIMENTAL CONTEXT - Andreea HOROIȚĂ; Adrian OPRE (Studia Universitatis Babeş-Bolyai. Psychologia-Paedagogia, 2022)
In times of pandemic and afterwards, online platforms and settings have been intensively used. With the purpose of investigating how this setting affected our memory, recent studies have found that memory distortions are present in online environments as well. Therefore, the objective of the present research was to assess misinformation effect in online context, more specifically to assess misinformation effect using leading questions and suggestibility techniques in online format. Our results indicate the presence of misinformation effect through suggestibility, but not through leading questions. Theoretical and practical implications are discussed.